2007
DOI: 10.1073/pnas.0706426104
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions in phospholipid membranes revealed by coherent 2D IR spectroscopy

Abstract: The inter-and intramolecular interactions of the carbonyl moieties at the polar interface of a phospholipid membrane are probed by using nonlinear femtosecond infrared spectroscopy. Twodimensional IR correlation spectra separate homogeneous and inhomogeneous broadenings and show a distinct cross-peak pattern controlled by electrostatic interactions. The inter-and intramolecular electrostatic interactions determine the inhomogeneous character of the optical response. Using molecular dynamics simulation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
3
36
0
3
Order By: Relevance
“…As a consequence, the spectral inhomogeneity decays with a comparatively slow rate, dictated by the time scale of the phospholipid rotational dynamics and lateral mobility. This long time scale inhomogeneity is similar to that observed for the carbonyl stretching modes reported elsewhere [21]. The complexity of water's optical response at the interface of dehydrated membranes [15] reflects the presence of several aqueous molecular forms.…”
supporting
confidence: 85%
“…As a consequence, the spectral inhomogeneity decays with a comparatively slow rate, dictated by the time scale of the phospholipid rotational dynamics and lateral mobility. This long time scale inhomogeneity is similar to that observed for the carbonyl stretching modes reported elsewhere [21]. The complexity of water's optical response at the interface of dehydrated membranes [15] reflects the presence of several aqueous molecular forms.…”
supporting
confidence: 85%
“…Mackenzie et al detected inter-helical contacts between nearby amides in the NMR structure of the TM domain of the homodimeric protein, glycophorin (13). This finding suggested that it might be possible to solve structures of membrane proteins by 2D-IR if two methodological and theoretical challenges could be met.…”
mentioning
confidence: 99%
“…Based on knowledge of the typical sequences of interacting regions of TM dimers (13) and mutagenesis studies of the αIIb homodimer (8) it was anticipated this region would encompass some amides on different helices that would have measurable interactions. We then applied 2D IR spectroscopy to micelle embedded samples of these peptides in solution.…”
mentioning
confidence: 99%
“…Ein 2DIR-Spektrum der C = O-Streckschwingung dieser Doppelschicht ist in Abbildung 22 gezeigt. [107] Die Entartung der sn-1-und sn-2-Carbonylgruppen wurde durch 13 C-Markierung der sn-2-Kette aufgehoben, sodass zwei breite Banden bei 1697 und 1740 cm À1 beobachtet wurden.…”
Section: Anwendungen Auf Phospholipide Quasipartikeldarstellung Von unclassified
“…[106] Righini und Mitarbeiter untersuchten die lokale Struktur von Lipiden in Dimyristoylphosphatidylcholin(DMPC)-Membranen durch Isotopenmarkierung der Carbonylgruppen der Membran. [107,108] Durch Signalformanalyse der 2D-Spektren der Amid-I-Banden (Streckschwingung der Rückgrat-Carbonylgruppen) von elf entlang eines Transmembranpeptidbündels ausgerichteten Aminosäureresten konnten Zanni et al die homogenen und inhomogenen Signalverbreiterungen bestimmen, die Auskunft über die Strukturverteilungen und die Pikosekundendynamik von Peptiden und deren Umgebung geben. [93] Auch 2DIR-Studien fehlgefalteter Peptidaggregate (Amyloidfibrillen) wurden beschrieben.…”
Section: Historische Entwicklungunclassified